Evaluation of the content of mathematics curricula for the intermediate stage in the light of visual thinking skills - Shweihi, Hassar bin Hassan bin Mohammed (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed at identify the evaluation estimates of the content of the book of maths for the intermediate stage in the light of visual thinking skills. The descriptive approach was used through analysis of content based on objective, structured and quantitative description of thinking skills. The study tool is developed by identifying visual thinking skills related to math study and necessary for middle school students.  The results of the study generally indicated that the content of mathematics books for middle school was interested in visual thinking skills in all middle-school grades. In short, middle school math books have made a clear effort, demonstrating the use of a lot of skills clearly and focusing on important skills for middle school students with visual thinking skills.
Keywords: evaluation; content; mathematics curricula; middle school; visual thinking skills